1996
DOI: 10.1002/(sici)1097-0142(19960501)77:9<1934::aid-cncr25>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Radiation alone for carcinoma of the vagina: Variation in response related to the location of the primary tumor

Abstract: This study discusses the curability of carcinoma of the vagina based on its anatomic location when predominantly similar treatment techniques and radiation doses were applied to either the proximal or the distal part of the vagina, those with cancer in the proximal half had better survival (81%) than those whose cancer was in the distal half (41%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The standard treatment is radiotherapy, which utilizes external beam radiation [EBRT] and/or brachytherapy [BT] techniques [6,22,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]. The addition of concurrent cisplatin-based chemotherapy has been recently incorporated in the treatment of this malignancy [62][63][64][65].…”
Section: Treatment Modalitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…The standard treatment is radiotherapy, which utilizes external beam radiation [EBRT] and/or brachytherapy [BT] techniques [6,22,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]. The addition of concurrent cisplatin-based chemotherapy has been recently incorporated in the treatment of this malignancy [62][63][64][65].…”
Section: Treatment Modalitiesmentioning
confidence: 96%
“…Radiotherapy is the mainstay of treatment for squamous cell carcinoma of the vagina [6,22,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]86]. Therapy plans are individualized and involve combinations of BT and EBRT, which is essential to ensure the delivering of a curative dose to the clinical target volume [CTV], may be intracavitary or interstitial, depending on the extent, thickness, location and morphology of the tumor.…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy is generally regarded as the treatment of choice and we must continue to improve our understanding of treatment techniques and results. The parameters that influence results of radiation treatment include stage [1][2][3], positive nodes [3,4], overall treatment time [2], location (proximal better than distal) [5], histopathology [6], and radiotherapy implant technique [4]. Two external-beam techniques are commonly used: the four-field (box) and the two-field (anterior and posterior) approach.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier authors like Kucera et al and Ali et al [15,16] have suggested that tumors of upper one-third or upper half of vagina behave better compared with lower-located tumors. Lian et al [5] also observed better DFS for lesions in upper third of vagina.…”
Section: Tumor Factorsmentioning
confidence: 99%